Interpretation of Dayak Ma’anyan Tribe’s Cultural Values Through Fables as Economic Development Strategic Plan - Nirena Ade Christy; Stefani Ratu Lestariningtyas; Ibnu Yustiya Ramadhan; Ade Yusuf Ferudyn (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to interpret the cultural values of the Dayak Maanyan tribe through fables an economic development strategic plan. This study used qualitative analysis and literature studies methods. This study aims to discover on how the Dayak Ma’anyan tribe's fables can be adapted to create economic opportunities through creative and digital products. The results of this study indicate that the cultural values in the Dayak Ma’anyan tribe's fables are not only important as cultural preservation, but also contain the potential to support sustainable economic development. The significance of this study lies in the application of cultural values in the Dayak Maanyan tribe's fables as a basis for relevant economic innovation.